Microstructures and Mechanical Properties of Al Matrix Composites Reinforced with TiO2 and Graphitic Carbon Nitride - Chen Wang; Xianyong Zhu; Ke Zhang; Jiaan Liu; Xiong Xiao; Cheng Jiang; Jinyuan Zhang; Changchun Lv; Zhaoxue Sun (Metals)
The scattering of reinforcement plays a crucial role in the microstructure and properties of metal matrix composites. In this study, an aluminum matrix composite (AMC) was reinforced by 10 wt% TiO2 (Al-10TiO2), with an average particle size of a submicron, combined with a different content of graphitic carbon nitride (g-C3N4), which was fabricated by shift-speed ball milling (SSBM) combined with multi-pass friction stir processing (FSP). In addition to the high hardness of TiO2, g-C3N4 has functional groups to promote in situ reactions. SSBM improves the distribution of reinforcement, refines grain size, and reduces the structural destruction of g-C3N4. The in situ reaction was achieved after multi-pass FSP at a high rotational speed and low travel speeds, which can promote uniform dispersion and grain refinement. Moreover, the g-C3N4 shows the efficient enhancement of strength while maintaining the elongation of AMC. Because the exfoliation of g-C3N4 under the effect of processing reduces the agglomeration of TiO2, boosts the flattening of Al, and enhances interface integration with the base metal. In situ phases can reduce the generation of coarse phases and improve interfacial bonding ability to enhance mechanical properties. The maximum tensile strength has been found at about 172.5 MPa in the Al-10TiO2 containing 1 wt% g-C3N4, which was enhanced by 34% compared to that of the Al-10TiO2. The tensile strength increases when the g-C3N4 content increases from 0 to 1 wt%, but then reduces with a further increase of content. The hardness was increased by 50.2%, 60.2%, and 35% with a g-C3N4 content of 0.5, 1, and 2 wt% compared to AMCs without reinforcement, respectively. According to the test, the enhancement mechanism is mainly attributed to Orowan, grain refinement strengthening, and load transfer of scattered reinforcement. In summary, the utilization of hybrid reinforcements successfully enhances the microstructure and mechanical properties.